Bilateral Cubonavicular and Synchronous Talocalcaneal Tarsal Coalition with Stress Response—Case Report and Review of Literature - Hussein, Mohsin; Metcalfe, Stuart; Iyengar, Karthikeyan P.; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2023)
Tarsal coalition occurs in 1% of the population and represents a congenital failure of segmentation in two or more tarsal bones. It most commonly occurs at the talocalcaneal and calcaneonavicular joint. Although commonly asymptomatic, it may present with pain, rigidity, and pes planus. Cubonavicular, multiple synchronous, and bilateral coalitions are rare but an awareness is required to ensure accurate diagnosis and management. In this article, we presented the first reported case (to the best of our knowledge) of bilateral cubonavicular coalition with synchronous talocalcaneal coalition and stress response within the intermediate cuneiform.
Keywords: coalition; tarsal; synchronous; stress response